Survey on Compass Shoes: The Influence of Social Media Marketing and Product Design on Repurchase Intention with Consumer Satisfaction as Mediator - Jayadi, Moch Zulfan; Setiawan, Rahyuniati; Maulani, Galih Abdul Fatah (Manunggal Halim Jaya, 2026)
This study analyzes the influence of Social Media Marketing (SMM) and Product Design on Repurchase Intention with Customer Satisfaction as a mediating variable among Compass shoe users, using a quantitative SEM-PLS approach with 107 respondents. The results indicate that SMM has a significant effect on Repurchase Intention, while Product Design significantly affects Repurchase Intention but not Customer Satisfaction, and Customer Satisfaction does not serve as a strong mediator in the relationship between Product Design and Repurchase Intention. These findings suggest that effective digital marketing strategies through social media are more capable of building loyalty and driving repurchase intention than relying solely on product design, although design remains crucial in shaping consumer perception and attractiveness. The R² value of 0.915 and Q² value of 0.767 confirm the model's excellent predictive power. The practical implication is that local fashion brands like Compass should optimize consumer interaction through social media by leveraging creative content, influencer collaborations, and #localpride narratives to strengthen brand image, while also developing design innovations that balance functional, aesthetic, and comfort aspects to enhance the overall customer experience. This demonstrates that customer satisfaction acts as an important bridge in reinforcing the impact of digital strategies on loyalty, making the integration of social media marketing and market-oriented product design a key factor in increasing repurchase intention and boosting the competitiveness of the local footwear industry.